The evolutionary origins of life and death - Durand, Pierre M. (Pierre Marcel) (University of Chicago Press, 2021)
"The question of why an individual would actively kill itself has long been an evolutionary mystery. Pierre Durand's ambitious manuscript answers this question through close inspection of life and death in the earliest cellular life. It turns out that cell death is a fascinating lens through which to examine the interconnectedness, in evolutionary terms, of life and death. It is a truism to note that one does not exist without the other, but just how does this play out in evolutionary history? These two processes have been studied from philosophical, theoretical, experimental, and genomic angles, but no one has yet integrated the information from these various disciplines. In this work, Durand synthesizes cellular studies of life and death looking at the origin of life, and the evolutionary significance of programmed cellular death.The exciting and unexpected outcome of Durand's work is the realization that life and death exhibit features of coevolution. The evolution of more complex cellular life depended on the coadaptation between traits that promote life and those that promote death. In an ironic twist, it becomes clear that, in many circumstances, programmed cell death is essential for sustaining life"--